1993
DOI: 10.1038/bjc.1993.254
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of MHC class I and II expression in relation to presence of HPV genotypes in premalignant and malignant cervical lesions

Abstract: Summary Cervical intraepithelial neoplasia (CIN) grades I to III lesions (n = 94) and squamous cell carcinomas of the uterine cervix (n = 27) were analysed for MHC class I and II expression and presence of HPV genotypes.MHC class I and II expression was studied by immunohistochemistry and HPV typing was performed by general primer-and type-specific primer mediated PCR (GP/TS PCR). Both A central role in the antigen-specific immune response is played by the major histocompatibility complex (MHC), which are ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
69
0

Year Published

1994
1994
2004
2004

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 110 publications
(71 citation statements)
references
References 23 publications
2
69
0
Order By: Relevance
“…Secondly, MHC class I alleles are down-regulated on the surface of neoplastic cells, as has been previously shown in several studies for both premalignant and malignant lesions (Connor and Stern, 1990;Cromme et al, 1993). This lower expression or even complete absence of MHC class I molecules on tumour cells could affect their recognition and lysis by CTLs (Rivoltini et al, 1995).…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…Secondly, MHC class I alleles are down-regulated on the surface of neoplastic cells, as has been previously shown in several studies for both premalignant and malignant lesions (Connor and Stern, 1990;Cromme et al, 1993). This lower expression or even complete absence of MHC class I molecules on tumour cells could affect their recognition and lysis by CTLs (Rivoltini et al, 1995).…”
Section: Discussionmentioning
confidence: 79%
“…An active role for the cellular immune system in the prevention of the development of cervical cancer is evidenced by a higher incidence of HPV-associated premalignant lesions in immunocompromised patients, such as AIDS patients and transplant recipients (Halpert et al, 1986;Laga et al, 1992). However, we and others have shown that major histocompatibility complex (MHC) class I expression is frequently down-regulated on neoplastic cells in malignant and premalignant lesions (Connor and Stem, 1990;Cromme et al, 1993;Honma et al, 1994;Keating et al, 1995). Lower expression or even complete absence of MHC class I molecules on tumour cells could affect their lysis by cytotoxic T cells as has been shown in melanomas (Rivoltini et al, 1995).…”
mentioning
confidence: 99%
“…Decreased HLA expression was not correlated with the presence of human papillomavirus 16 or 18 in cervical cancers (Cromme et al, 1993a). It has been suggested that down-regulation of class I MHC expression in cervical cancers is apparently post-transcriptionally controlled (Cromme et al, 1993b).…”
Section: Introductionmentioning
confidence: 93%
“…56 Briefly, five consecutive sections (4 m) were suspended in 150 l of digestion buffer containing 1% SDS, 0.5 M Tris-HCl, 20 mM EDTA, 10 mM NaCl and proteinase K (2 l of 20 mg/ml stock solution). Samples were incubated with shaking at 56°C for 12 to 24 hr followed by inactivation of proteinase K at 96°C for 10 min.…”
Section: Dna Isolation and Hpv Typingmentioning
confidence: 99%